2020
DOI: 10.1021/acs.chemmater.0c02290
|View full text |Cite
|
Sign up to set email alerts
|

Database of Two-Dimensional Hybrid Perovskite Materials: Open-Access Collection of Crystal Structures, Band Gaps, and Atomic Partial Charges Predicted by Machine Learning

Abstract: We describe a first open-access database of experimentally investigated hybrid organic-inorganic materials with two-dimensional (2D) perovskite-like crystal structure. The database includes 515 compounds, containing 180 different organic cations, 10 metals (Pb, Sn, Bi, Cd, Cu, Fe, Ge, Mn, Pd, Sb) and 3 halogens (I, Br, Cl) known so far and will be regularly updated. The database contains a geometrical and crystal chemical analysis of the structures, which are useful to reveal quantitative structure-property re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
155
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(156 citation statements)
references
References 38 publications
1
155
0
Order By: Relevance
“…[11] It should be noted that compositions of the type APbBr 4 , A 2 PbBr 4 or AA'PbBr 4 have, in principle, a choice between adopting (100)-cut structure types (i. e. Ruddlesden-Popper or Dion-Jacobson families) or the (110)-cut family. A recent comprehensive review of the (100)-cut families reported more than 250 examples, [12] whereas recent works, including an on-line database, [13] suggest only around 20 examples of the (110)-cut family. Moreover, it has been noted that (110)-derived materials can offer particularly useful physical properties, such as broadband emission, due to their often higher degrees of distortion of the inorganic layers and greater degree of electronic confinement.…”
Section: Introductionmentioning
confidence: 99%
“…[11] It should be noted that compositions of the type APbBr 4 , A 2 PbBr 4 or AA'PbBr 4 have, in principle, a choice between adopting (100)-cut structure types (i. e. Ruddlesden-Popper or Dion-Jacobson families) or the (110)-cut family. A recent comprehensive review of the (100)-cut families reported more than 250 examples, [12] whereas recent works, including an on-line database, [13] suggest only around 20 examples of the (110)-cut family. Moreover, it has been noted that (110)-derived materials can offer particularly useful physical properties, such as broadband emission, due to their often higher degrees of distortion of the inorganic layers and greater degree of electronic confinement.…”
Section: Introductionmentioning
confidence: 99%
“…updated. [62] The database contains structural and chemical information and offers a useful data source for developing quantitative structure-property relationships for the 2DHPs, as shown by the developed machine learning models for the prediction of bandgaps and atomic partial charges in the study by Mitzi. [62] Next, we review experimental characterization of the structural properties for several common types of 2DHPs: 1) perovskites containing long chain organic molecules and MA; 2) perovskites containing aromatic ring molecules; 3) perovskites containing MA only; 4) perovskites containing dimethylammonium (DMA); and 5) newly discovered ACI perovskites.…”
Section: Structuresmentioning
confidence: 99%
“…In addition, it is worth mentioning that an open‐access database of the 2DHPs that includes over 500 compounds has been reported in a very recent work and is being regularly updated. [ 62 ] The database contains structural and chemical information and offers a useful data source for developing quantitative structure–property relationships for the 2DHPs, as shown by the developed machine learning models for the prediction of bandgaps and atomic partial charges in the study by Mitzi. [ 62 ]…”
Section: Structuresmentioning
confidence: 99%
“…The broadest order of hybrid organic–inorganic quasi‐2D perovskite‐like structures [ 20 ] could be imagined by slicing off layers from ABX 3 perovskites framework along the (100), (110), or (111) directions with organic cations serving as spacers. The (100)‐oriented cleaves lead to the mostly studied Ruddlesden–Popper (RP) and Dion–Jacobson (DJ) families.…”
Section: Introductionmentioning
confidence: 99%